Faktor-Faktor Yang Berhubungan Dengan Minat Masyarakat Mengikuti Vaksinasi COVID-19 Di Desa Kebun Kelapa : FACTORS RELATED TO PUBLIC INTEREST IN PARTICIPATING IN COVID-19 VACCINATION IN THE KEBUN KELAPA VILLAGE - Ani Rahmadhani Kaban; Hizrah Hanim Lubis; Siregar, Maya Ardilla (Intan Husada : Jurnal Ilmiah Keperawatan, 2023)
Background Corona virus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Most the people who contracted the COVID-19 had has experience mild to moderate symptoms, and will recover without special treatment. Purpose This research was going to find out the factors related to people's interest in taking the COVID-19 vaccination in Kebun Kelapa Village in 2022. The design This study used an analytical survey method with a cross sectional approach. This research was conducted in Kebun Kelapa Village. The population in this research was the people in Kebun Kelapa Village, totaling 3094 people. The sampling technique was accidental sampling using the slovin formula, namely 97 respondents using unviariat and bivariate analysis using the chi-square test. The results research conducted using the chi-square test on occupations with an interest in participating in the COVID-19 vaccination p-value = 0.003, knowledge p-value = 0.000, attitude p-value = 0.005 and age p-value = 0.001. The conclusion in this research in this study shows that there is a significant relationship between work, knowledge, attitudes, and age with an interest in taking the COVID-19 vaccination in Kebun Kelapa Village in 2022. It is suggested that it can be used as input and information to the community in Kebun Kelapa Village so they can take the COVID vaccination -19